A New Design of an UWB Circular Fractal Printed Antenna - Akram El Hamdouni; Abdelali Tajmouati; Jamal Zbitou; Ahmed Errkik; Larbi El Abdellaoui; Mohamed Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
A Microstrip Antenna (MSA) has been computed and analysed in this study by using CST of Microwave studio as Electromagnetic solver by generating the coefficient of reflection, the Gain, the density of current and the radiation pattern in the frequency range 3.1-10.6 GHz which commercialised by the Federal communication commission (FCC) as an Ultra-wide band (UWB) frequency range. The substrate used to achieve the proposed structure is the FR4-Epoxy with a thickness of 1.6 mm, a constant dielectric of 4.4 and a loss tangent of 0.025. The radiating patch is a circular shape etched with different sizes to create the fractal geometry. The transmission line has been designed by including a tapered section in the part connected to the radiator. The design of the antenna has been verified by using ADS and CST solvers. The fabrication of the antenna has been performed in order to measure the coefficient of reflection and the radiation pattern.